2020
DOI: 10.15203/ciss_2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Model of Olympic Social Capital: Theory and Early Evidence

Abstract: Towards a model of Olympic social capital: Theory and early evidence Social capital in sports has become an increasingly studied topic. In particular, it has been argued that social capital is created by value-based cultural practices and social exchanges with respect to sport participation and sporting events. However, empirical evidence is scarce and does not capture causal relationships in the process of social capital creation. A general criticism in the social capital literature is that the existing theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 80 publications
2
8
0
Order By: Relevance
“…In comparison with similar education initiatives, Schnitzer et al (2018) found an increase in local interest in the Olympic Movement in Singapore, while Grammatikopoulos et al (2005) noted positive effects in teacher relationships and training as a result of the Olympic education program in Greece. This is also consistent with recent studies in which knowledge about teaching Olympism , simultaneous experience, and social exchange (Prüschenk and Kurscheidt 2020) contribute to the development of social capital as a particularly suitable platform to leverage the Games' intangible legacy (Griffiths and Armour 2013). In this sense, one may argue that when the Olympic Games are embedded in educational practices, social capital formation occurs over time, leading to a positive and intangible outcome.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In comparison with similar education initiatives, Schnitzer et al (2018) found an increase in local interest in the Olympic Movement in Singapore, while Grammatikopoulos et al (2005) noted positive effects in teacher relationships and training as a result of the Olympic education program in Greece. This is also consistent with recent studies in which knowledge about teaching Olympism , simultaneous experience, and social exchange (Prüschenk and Kurscheidt 2020) contribute to the development of social capital as a particularly suitable platform to leverage the Games' intangible legacy (Griffiths and Armour 2013). In this sense, one may argue that when the Olympic Games are embedded in educational practices, social capital formation occurs over time, leading to a positive and intangible outcome.…”
Section: Discussionsupporting
confidence: 89%
“…The current approach to the Olympics legacy includes education as a way to promote the social capital created by cultural practices and social exchanges (Prüschenk and Kurscheidt 2020) such as education programs. Every host city commits to carrying out Olympic education programs as part of their responsibilities for organizing the Games (Binder and Naul 2017) and as a long-term social development process (Maya 2017), with three assumptions underlying these programs: First, Olympism should be used as an educational tool to influence behaviors based on cognitive (intellectual), affective (social/emotional), and kinesthetic (physical) learning (IOC 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman (1988) highlights the importance of increased social capital as part of educational outcomes, referring to a set of attributes (education, skills, knowledge, and personal experiences) as ways to enhancing the productivity and competitive advantages. The social capital of individuals is enhanced when using and transferring Olympic knowledge (Prüschenk & Kurscheidt, 2020).…”
Section: Social Capital As a Legacymentioning
confidence: 99%
“…The social capital generated by the Olympic Games can be explored on the basis of three attributes (Prüschenk & Kurscheidt, 2017): bonding, bridging, and linking capital. Bonding is typically found in smaller, strongly interconnected, and homogeneous communities (Prüschenk & Kurscheidt, 2020), which may apply to the teachers of the Olympic education programmes because they have shared the same experiences, have met the same requirements, and have pursued the same objectives of teaching the Olympic values. Bridging is linked to the interrelations that stem from the Olympic Games and associated social ties driven by delivering the Olympic education programmes.…”
Section: Social Capital As a Legacymentioning
confidence: 99%